Landscapes, Myths and Artifacts - Mariella Zoppi (Agathón)
The synergy between people’s labour and the earth has generated the magnificence of the landscapes which we have inherited from previous generations. Today, their safeguard has to be linked to the capacity to plan their transformations. This is an ethical duty which needs to be aligned with the cultural, technical and political capacities in order to foster their balanced socioeconomic development.